(untitled) (Economic and Political Thought, 2014)
The article aims to present the effects of the accession of Poland to the European Union against a broader background of international relations and the context of changes that took place in the EU in the last decade. Thus, we deal with a specific balance of successes and failures Poland experienced in the period 2004–2014. The article shows that, twenty-five years after the political transformation in Poland and ten years after the accession to the European Union, our membership in that specific, voluntarily integrated union of sovereign European states undoubtedly proved to be necessary and inevitable. Thus, it is the basic thesis of this article. It was the only appropriate solution for Poland that resulted from its geopolitical location and historical experiences. Against all odds, it has not harmed our sovereignty and national identity. The author emphasises that the membership in the European Union has strengthened Poland’s sovereignty and serves Polish national interest. It has a positive impact on Poland’s economy and strengthens its prestige on the international arena.